Diagnosis of Helicobacter pylori‐induced gastritis by serum pepsinogen levels. Issue 10 (October 2015) - Kitamura, Yoko; Yoshihara, Masaharu; Ito, Masanori; Boda, Tomoyuki; Matsuo, Taiji; Kotachi, Takahiro; Tanaka, Shinji; Chayama, Kazuaki
Abstract Background and Aim Gastric cancer develops due to atrophic gastritis induced by Helicobacter pylori (H. pylori) infection. Serum levels of pepsinogen (PG) are known to be excellent markers for evaluating the degree of atrophic gastritis. We investigated whether chronic gastritis could be diagnosed by evaluating serum PG levels. Methods A total of 4483 patients (average age, 49.7 years; 2879 men) were included in this study. Fasting serum samples were collected and anti‐H. pylori antibody and PG levels were evaluated. We evaluated the endoscopic atrophy grade or histological extent of gastritis, and calculated the diagnostic capability of this serum marker. Results A total of 4483 patients, were diagnosed as being positive (4160) or negative (323) for H. pylori‐induced gastritis. In patients with H. pylori‐induced gastritis, the PG II levels were higher and the PG I/II ratios were lower than among those without H. pylori gastritis. A cut‐off values of (i) PG I/II ≤ 5; (ii) PG II ≥ 10 or PG I/II ≤ 5; (iii) PG II ≥ 12 or PG I/II ≤ 4.5 showed high sensitivity and accuracy (over 90%) for diagnosing H. pylori‐induced gastritis. Moreover, in a mass screening of healthy subjects, a cut‐off value of PG I/II ≤ 4.5 might be better for diagnosing the presence of gastritis because of a sensitivity and specificity > 80%. Conclusions The presence of H. pylori‐induced gastritis can be evaluated using serum PG levels.